Pengaruh Strategi Experiential Learning dan Kecerdasan Emosional Terhadap Hasil Belajar Menulis Puisi Siswa Kelas VII SMP Negeri 9 Pekanbaru - Zuraida (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
Writing poetry is a capable skill that involves students inner experiences. In learning to write poetry, students emotional intelligence also needs to be considered. Therefore, these variables are important to examine in order to see how much influence they have on students poetry writing skills. The type of research is quantitative research using quasi-experimental methods in the form of factorial designs. The population of this study was students of class VII SMPN 9 Pekanbaru, which consisted of 9 classes. Data were collected through learning achievement tests and analyzed by T-test and ANOVA. The results of the data analysis show that: (1) the results of learning to write poetry of students who are taught with experiential learning strategies are higher than students who are taught conventionally; (2) the learning outcomes of students with high emotional intelligence who are taught using experiential learning strategies are higher than students who are taught conventionally; (3) the learning outcomes of students with low emotional intelligence who are taught using experiential learning strategies are higher than students who are taught conventionally; (4) there is no interaction between learning strategies and emotional intelligence in influencing students learning outcomes in writing poetry. The conclusion is that the experiential learning strategy has a significant effect on the learning outcomes of students poetry writing. Students who have low emotional intelligence should use a variety of learning strategies.